Dramaturgi Penjualan: Pengelolaan Kesan dan Presentasi Diri dalam Praktik Pemasaran Langsung di Era Modern - UMMI SALAMAH SITORUS (Universitas Persada Indonesia YAI, 2026)
This article examines the application of Erving Goffman’s dramaturgy theory in the context of direct marketing in the modern era. The dramaturgical approach, which views social interaction as a theatrical performance, provides a relevant analytical framework for understanding how sales agents manage impressions and present themselves to consumers. Through a systematic literature review and survey data analysis involving 200 direct marketing agents in Indonesia, the study found that structured dramaturgical strategies, including the management of physical appearance, personal narratives, emotional control, role flexibility, and setting mastery, significantly enhance sales effectiveness compared to conventional approaches. The dimension of emotional expression management demonstrated the highest level of effectiveness (81%), followed by setting mastery (78%) and physical appearance (72%). These findings confirm that the success of direct marketing depends not only on product quality but also on the agent’s ability to “perform roles” authentically and adaptively. The theoretical and practical implications of this study are discussed within the framework of relational marketing in the digital era.